Cooperativas escolares e suas contribuições para a educação integral: a experiência das escolas municipais de ensino fundamental da região Centro Serra (RS) - Cazarolli, Micheli (2021)
Tarting from the premise that the 21st century presents a need for a different look at education, especially in basic education, with the relationship between teachers, curriculum content and students, this study aims to analyze an educational proposal of school cooperatives and their contribution for integral education in municipal elementary schools in the Centro Serra - RS. An analysis was supported by democracy conceptions from John Dewey (1859-1952), cooperation from Célestin Freinet (1896- 1966) and complex thought from Edgar Morin (1921-), which converge with the concept of integral education assumed by the BNCC and which qualifies the learning process through the development of different human dimensions. The qualitative study was carried out in three stages: bibliographical research, in order to build a theoretical framework; documentary research, which bases the data analysis; and the field search of the type study of case. For data collection, it was decided to divide the study into two formats: focus groups, including advisor professors and associate students in positions of president and vice president, and the application of semi-structured questionnaires to other associate students and active professors in by the last years of elementary school. With the research, it's recognized that school cooperatives follow an inverse path to the compartmentalization of knowledge and the reductionist view of education, having their proposal validated by the PPPs of educational institutions for corroborating the mission, vision and objectives of each one. As a result of the set of perceptions of the participating subjects, it was observed that the pedagogical practices proposed by the school cooperatives contribute to integral education by stimulating the experience of democracy, cooperation and the development of autonomy and the protagonism of the associated students.